2010
DOI: 10.7205/milmed-d-09-00047
|View full text |Cite
|
Sign up to set email alerts
|

Corrective Lens Use and Refractive Error Among United States Air Force Aircrew

Abstract: Corrective lens use by military aviators is an important consideration in the design of head-mounted equipment. The United States Air Force (USAF) has periodically monitored lens use by aviators; however, it has been over a decade since the last study. We provide an update on the prevalence of corrective lenses and refractive error among USAF aircrew based on eyeglass orders processed through the Spectacle Request Transmission System (SRTS). Currently, 41% of active duty USAF pilots and 54% of other aircrew re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The myopia prevalence is comparable to a recent study performed by Wright and colleagues, which demonstrated that 41% of active duty USAF pilots utilize corrective lenses. 20 Furthermore, it is similar to the analysis by Vitale and colleagues, who demonstrated an estimated prevalence of 41.6% in those aged 12-54 within the United States population. 21 The results presented do, however, demonstrate higher values of myopia than another recent study examining refractive error amongst active duty service members of all United States Armed Forces branches from 2001 to 2018, which demonstrated a crude annual lifetime prevalence of 38.5% for myopia (<−0.5D).…”
Section: Discussionsupporting
confidence: 87%
“…The myopia prevalence is comparable to a recent study performed by Wright and colleagues, which demonstrated that 41% of active duty USAF pilots utilize corrective lenses. 20 Furthermore, it is similar to the analysis by Vitale and colleagues, who demonstrated an estimated prevalence of 41.6% in those aged 12-54 within the United States population. 21 The results presented do, however, demonstrate higher values of myopia than another recent study examining refractive error amongst active duty service members of all United States Armed Forces branches from 2001 to 2018, which demonstrated a crude annual lifetime prevalence of 38.5% for myopia (<−0.5D).…”
Section: Discussionsupporting
confidence: 87%
“…It is well known that refractive devices in the aerospace environment negatively affect visual performance (Partner et al. 2005) (Wright et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Laser in situ keratomileusis (LASIK): LASIK is currently the most prevalent refractive surgery technique, offering faster rehabilitation and less discomfort [ 20 ] . After its approval by the USAF in May 2007, over 2200 aircrew underwent LASIK in 2010 [ 54 ] . Studies on LASIK eyes exposed to short-term hyperbaric hypoxia revealed only minor refractive changes, as presented in Table 1 [ 55 - 58 ] .…”
Section: Resultsmentioning
confidence: 99%